2012
DOI: 10.48550/arxiv.1211.2685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causality of spacetimes admitting a parallel null vector and weak KAM theory

E. Minguzzi

Abstract: The causal spacetimes admitting a covariantly constant null vector provide a connection between relativistic and non-relativistic physics. We explore this relationship in several directions. We start proving a formula which relates the Lorentzian distance in the full spacetime with the least action of a mechanical system living in a quotient classical space time. The timelike eikonal equation satisfied by the Lorentzian distance is proved to be equivalent to the Hamilton-Jacobi equation for the least action. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…Eisenhart [27] realized that the spacelike geodesics of (M, g) project to E := T × Q into solutions of the above Euler-Lagrange equation and that any such solution can be regarded as such projection. The author showed that the same can be said with spacelike replaced by lightlike [28], a fact particularly useful for its connection with causality theory [28,31,32]. Thus there is a very fruitful oneto-one correspondence between generalized gravitational waves and rheonomic mechanical systems, which allows one to import methods and ideas from one field to the other [32].…”
Section: Application To Lagrangian Mechanics and Gravitational Wavesmentioning
confidence: 95%
See 2 more Smart Citations
“…Eisenhart [27] realized that the spacelike geodesics of (M, g) project to E := T × Q into solutions of the above Euler-Lagrange equation and that any such solution can be regarded as such projection. The author showed that the same can be said with spacelike replaced by lightlike [28], a fact particularly useful for its connection with causality theory [28,31,32]. Thus there is a very fruitful oneto-one correspondence between generalized gravitational waves and rheonomic mechanical systems, which allows one to import methods and ideas from one field to the other [32].…”
Section: Application To Lagrangian Mechanics and Gravitational Wavesmentioning
confidence: 95%
“…The author showed that the same can be said with spacelike replaced by lightlike [28], a fact particularly useful for its connection with causality theory [28,31,32]. Thus there is a very fruitful oneto-one correspondence between generalized gravitational waves and rheonomic mechanical systems, which allows one to import methods and ideas from one field to the other [32].…”
Section: Application To Lagrangian Mechanics and Gravitational Wavesmentioning
confidence: 95%
See 1 more Smart Citation
“…In [8, Thm. 6.9] (see also [24]) the authors provide mild conditions under which a plane wave is causally continuous. So, according to Corollary 6.4, these conditions joined to the previously cited ones for geodesic completeness ensure that a plane wave has no black holes.…”
Section: Appendixmentioning
confidence: 99%
“…In addition to elucidating the symmetries, of and equivalences between, dynamical systems the Eisenhart-Duval construction offers the prospect of applying global techniques in Lorentzian geometry and causal theory to the dynamical systems which are their shadows [12,13].…”
mentioning
confidence: 99%